A metric space for semantic containment: Towards the implementation of genetic firewalls. (November 2019) - Schmidt, Markus
Abstract: Analysing or engineering the genetic code has mainly been considered as an approach to reduce or increase the mutational robustness of the genetic code, i.e. the error tolerance in DNA mutations, or to enable the incorporation of non-canonical amino acids. The approach of "semantic containment", however, is less interested in altering the mutational tolerance of the standard code, but to create synthetic alternative genetic codes that limit or all together impede horizontal gene transfer between a natural and genomically recoded organisms (GRO). A major claim or conjecture of semantic containment is: "the farther, the safer", meaning, the less similarity there is between two codes, the less chance of a horizontal gene transfer, and the stronger the genetic firewall. So far, no metrics were available to measure and quantify the "genetic distance" between different genetic codes. Such a metric, however, is iis paramount to allow the experimental testing and evaluation of the validity of semantic biocontainment for the first time. Here, we introduce a metric space to measure exactly the distance (dissimilarity) between different genetic codes, in order to provide a framework to evaluate the relation between distance and strength of a genetic firewall. Results are presented that incorporate bespoken metrics when producing alternative genetic codes according to predefined goals, specifications and limitations. Finally, as an outlook, implications and challenges for genetic firewall(s) are discussed for dual- and multi-code systems.